Meningkatkan Hasil Belajar Pak Dengan Model Pembelajaran Discovery Learning Melalui Media Gambar Fase D Tema Aku Pribadi Yang Unik Kelas VII SMP Santo Mikael Kota Cimahi - Damianus Unyir (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
Classroom Action Research was conducted to find out to what extent students can improve their learning outcomes both through group work activities in the mutual cooperation dimensions and formative tests, from the aspects of knowledge, affective and psychomotor. Learning activities and assessments are an important part of a learning process. Conversely, if the learning process is not well prepared and structured, of course the results will not be optimal, especially in this study using an independent curriculum which allows students to find problems that arise with the discovery learning model, students are invited to be able to find and process the material they learn. Therefore the teacher must be able to plan, design, implement and evaluate or reflect on a lesson that will be carried out so that learning outcomes are maximized, both in terms of cognitive and affective. So after seeing the results of the Pancasila student profile the dimensions of mutual cooperation in the first cycle were 77.00% and in the second cycle 81.94% increased by 4.94% and while the formative value of test 1 with an average of the first cycle was 71.30% increased in the first cycle second with an average value of 85.48%. So with the increase in the results of formative assessments 1 and 2 with the Discovery Learning model, especially in Class VII PAK Lessons at Santo Mikael Middle School, it further adds to the enthusiasm of students in learning because students are able to find problems and solve them.